STRATEGI PENGELOLAAN DENGAN ANALISIS SWOT PADA EKOWISATA MANGROVE KAMPUNG NIPAH, KABUPATEN SERDANG BEDAGAI, SUMATERA UTARA - Novi Aulia Sari Aulia; Futri Anggraini Futri; Maghfira Rahmadani Fira; Nezeliana Putri Nezel (Jurnal Samudra Geografi, 2023)
This study aims to explain the legal aspects, to find out the zone of existence of the Kampong Nipah mangrove ecotourism object and to describe the management strategy of mangrove ecotourism. The method used in this research is using purposive sampling and accidental sampling. In this study using data analysis techniques, namely, document content analysis and SWOT analysis. The results of this study indicate that the development of mangrove ecotourism in Kampung Nipah already has a legal status to serve as a tourist spot. The resulting strategies are 5, namely: Improving infrastructure in the form of adding trash cans, revitalizing bridges, carrying out waste management with an integrated community-based management system that involves the surrounding community, increasing diversification of ODTW (tourist attraction objects), increasing promotion through publications and joint ventures. with tourism developers.